Biomimetic Nanomaterials Triggered Ferroptosis for Cancer Theranostics - Zhang, Xinyu; Ma, Yanling; Wan, Jipeng; Yuan, Jia; Wang, Diqing; Wang, Weiyi; Sun, Xiao; Meng, Qingwei (Frontiers in Chemistry, 2021)
Ferroptosis, as a recently discovered non-apoptotic programmed cell death with iron-dependent form, has attracted great attention in the field of cancer nanomedicine. However, many ferroptosis related nano-inducers encountered unexpected limitations, such as immune exposure, low circulation time, and ineffective tumor targeting. Biomimetic nanomaterials possess some unique physicochemical properties which can achieve immune escape as well as effective tumor targeting. Especially, certain components of biomimetic nanomaterials can further enhance ferroptosis. Therefore, this review will provide a comprehensive overview on recent developments of biomimetic nanomaterials in ferroptosis-related cancer nanomedicine. First, the definition and characteristic of ferroptosis and its current applications associates with chemotherapy, radiotherapy and immunotherapy for enhancing cancer theranostics were briefly discussed. Subsequently, the advantages and limitations of some representative biomimetic nanomedicine, including bio-membrane, protein, amino acid, polyunsaturated-fatty-acids, and biomineralization based ferroptosis nano-inducers, were further spotlighted. This review would therefore help the spectrum of advanced and novice researchers interested in this area to quickly zoom in the essential information and glean some provoking ideas to advance this sub field in cancer nanomedicine.